Pengujian Performa Website Resmi Klub Sepakbola Persib Bandung Menggunakan Tools GTmetrix - Shulhi Fifuadiuadi (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
Abstract The more the times develop, the more various media as a source of information and communication. One of them is the Website, the website is very important as a source of information and communication. In the world of sports especially football, a website is very important for a professional football club. The website is useful to convey information or official news from the club itself which can later be read by supporters or the public. Therefore, website performance is very important for the sustainability of many people in accessing it. So that the website performance test is carried out using the GTmetrix tool. The purpose of the research is to present the performance of the website. Based on performance testing using GTmetrix obtained grade D with details of Performance 57% while Structure 69%.